A Comparative Study of the Common Protozoan Parasites of Clarias gariepinus from the Wild and Cultured Environments in Benue State, Nigeria. (18th October 2011) - Omeji, S.; Solomon, S. G.; Idoga, E. S.
Abstract : A total of one hundred and twenty Clarias gariepinus comprising 30 dead and 30 live fishes were examined for protozoan parasites infestation, sixty each from the wild and a pond (cultured environment) over a period of six months. Ichthyophthirius multifiliis was the most common protozoan parasites found in C. gariepinus from the wild (River Benue) and cultured (pond) environments. These protozoan parasites constitute 37.08% of the total parasites encountered for fishes in the pond and 42.51% of fishes in the wild. Among the body parts of the sampled fishes from the pond, the gills had the highest parasite load (38.86%). Also, the gills had the highest parasite load (40.54%) among the body parts of the fishes sampled from the wild. Fishes not infested with any protozoan parasites from the pond constituted 36.70% of the total fish sampled. On the other hand, fishes not infested with any protozoan parasites from the wild constituted 31.65% of the total fish sampled. Female fishes had more protozoan parasites than the male fishes. Bigger fishes of total length (25–48 cm) had more parasite load than the smaller ones (19–24 cm). Also, fishes between 150–750 g had more parasite load than the smaller ones of less than 150 g. Protozoan parasite load of fish from the cultured environment (pond) did not differ significantly (P < 0.05 ) from those from River Benue (wild).